Assessment of organohalogenated pollutants in breast milk from the Czech Republic - Parizek, Ondrej; Gramblicka, Tomas; Parizkova, Denisa; Polachova, Andrea; Bechynska, Kamila; Dvorakova, Darina; Stupak, Michal; Dusek, Jiri; Pavlikova, Jitka; Topinka, Jan; Sram, Radim J; Pulkrabova, Jana (The Science of the total environment, 2023)
This biomonitoring survey brings new information on the occurrence of a total of 94 organohalogenated pollutants in 231 human breast milk samples collected in 2019 and 2021 from women living in two regions of the Czech Republic (Karvina and Ceske Budejovice). This study aimed to evaluate the concentrations of 6 indicator polychlorinated biphenyls (PCBs), 10 organochlorine pesticides (OCPs), 34 halogenated flame retardants (HFRs), 29 perfluoroalkyl and polyfluoroalkyl substances (PFAS) and 15 polychlorinated naphthalenes (PCNs). PCBs, OCPs, most of HFRs and PCNs were identified/quantified by gas chromatography coupled to (tandem) mass spectrometry (GC-MS(/MS)), while PFAS, hexabromocyclododecane isomers (HBCD), brominated phenols, and tetrabromobisphenol A (TBBPA) by ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). The mean value of the sum of the 6 indicator PCBs was 123.12 nanogram per gram of lipid weight (ng g-1 lw). Hexachlorobenzene (HCB), β-hexachlorocyclohexane (β-HCH) and p,p'-dichlorodiphenyl-dichloroethylene (p,p'-DDE) were the most abundant OCPs, detected in 100 % (mean 11.8 ng g-1 lw), 94.8 % (mean 6.1 ng g-1 lw) and 100 % (mean 101.5 ng g-1 lw) of samples, respectively. PCN congeners 20, 52 and 66 were detected in <1 % of the samples. The HFRs concentrations were relatively low compared to the levels of OCP; The detection rate of polybrominated diphenyl ethers (PBDEs, # 47, 99 and 153) ranged 21-68 % with a mean concentrations of 0.34 ng g-1 lw - 0.42 ng g-1 lw. PFAS concentrations were also low, with perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) dominant in this group (means of 22 pg ml-1 and 21 pg ml-1, respectively). Our results confirmed the long-term trend of declining levels of banned POPs in Czech mothers. The amounts of PCBs and OCPs were higher in older breastfeeding primiparous women.
Keywords: senioři; Environmental Pollutants; látky znečišťující životní prostředí; monitorování životního prostředí; PCBs, PFAS; HFRs; polychlorované bifenyly; Milk, Human; Česká republika; dichlordifenyldichlorethylen; halogenované difenylethery; Environmental Monitoring; Pesticides; fluorokarbony; Czech Republic; retardanty hoření; Fluorocarbons; Polychlorinated Biphenyls; ženské pohlaví; mateřské mléko; Humans; Tandem Mass Spectrometry; Halogenated Diphenyl Ethers; chlorované uhlovodíky; Human biomonitoring, risk assessment; Flame Retardants; Dichlorodiphenyl Dichloroethylene; Hydrocarbons, Chlorinated; tandemová hmotnostní spektrometrie; OCPs; pesticidy; Female; Aged; lidé